Analisis Lingkungan Lembaga Pendidikan Islam - Binti Nasukah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2017)
Islamic Education Institutions (IEIs), as a part of social system life, need to be aware of their environment. They have to realize that the existence of environment’s elements around them, determine their sustainability. Therefore, it is a necessity to implement environment analysis. Using literature studies, this article tries to analyzing environment’s elements of IEIs, both internal and external. It is hoped that article will give perspective to IEIs’ manager about the importance of environment analysis and be guidance for a manager who wants to execute environment analysis.